The relationship between physical activities and student’s academic performance / Nik Norhaslizawati Nik Muhammad, Nur ‘Atiqah Imani Adam Sakeri and Nurul Ayuni Abdul Aziz - Nik Muhammad, Nik Norhaslizawati; Adam Sakeri, Nur ‘Atiqah Imani; Abdul Aziz, Nurul Ayuni (2012)
The research is about conducting a process involved with dependant variables identified that affect the student’s academic performance. This research is generally to identify the relationship between physical activities and student’s academic performance at University Technology Mara Dungun Campus. Basically, this research focuses more on the factors that affect the performance of student based on type, the frequency, and the area or place to do the physical activities. A set of questionnaires have been distributed in order to find the result and from the data collected, we know the actual relationship between physical activities and student’s academic performance. The respondents for this research are student from part one to part six of three faculties which are Office System Management, Hotel Management, and Accounting Management of the UiTM Dungun Campus. For this research, the researchers used the mean, standard deviation, frequency, percentage, and Pearson’s correlation for analze the data received. So by that, the researchers received the actual result and according to the result in Pearson correlation, the researchers can conclude that there are relatioship between physical activities and student’s academic performance. The conclusion for this study, some decision will be taken in order to improve student’s academic performance through their physical activities that they have been chosen. Entirely, the findings regarding this research is to ensure the students do the right physical activities which are affect their academic performance for UiTM Dungun Campus.